Phytochemical Analysis and Evaluation of Bioactivities of Artemisia vulgaris Solvent Extracts - Gautam, Sijan; Bhusal, Manisha; Magar, Akash Budha; Basnyat, Ram Chandra; Parajuli, Niranjan; Sharma, Khaga Raj (Journal of Institute of Science and Technology, 2024)
Artemisia vulgaris, a prominent medicinal species within the genus Artemisia, has drawn significant scientific interest due to its rich composition of biologically active secondary metabolites. This study evaluates the phenolic and flavonoid content, antioxidant, α-glucosidase inhibitory, and antimicrobial activities of Artemisia vulgaris, sourced from Khaptad National Park at an elevation of 2907 meters. Different solvent fractions, including water, methanol, dichloromethane (DCM), ethyl acetate + hexane, and hexane, were used for the extraction of phytochemicals as secondary metabolites. Methanol and water extracts exhibited the highest total phenolic content (TPC), with values of 54.40 ± 1.55 mg GAE/g and 50.29 ± 1.69 mg GAE/g, respectively. The highest total flavonoid content (TFC) was observed in methanol and DCM extracts, measuring 42.31 ± 1.83 mg QE/g and 19.96 ± 0.89 mg QE/g, respectively. Methanol extracts demonstrated the strongest antioxidant activity, with a DPPH radical scavenging IC50 of 19.00 ± 0.81µg/mL, followed by DCM extracts at 25.90 ± 0.76 µg/mL. The methanol extract also exhibited the most potent α-glucosidase inhibition, with an IC50 of 63.23 ± 0.20 µg/mL, while DCM, water, and ethyl acetate + hexane extracts showed lower activity. Antimicrobial analysis revealed inhibition of Staphylococcus aureus with zones of inhibition (ZOI) of 9 mm for methanol and 5 mm for DCM extracts, and a ZOI of 4 mm for Escherichia coli with methanol extract. Results suggest that Artemisia vulgaris imparts the potential effect, particularly in antioxidant and antibacterial activities, underscoring its therapeutic potential. The plant could be used as a source of natural antioxidant and antibacterial agents for isolating the target compounds in the future drug development process.